The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008 IEEE Pacific Visualization Symposium 2008
DOI: 10.1109/pacificvis.2008.4475461
|View full text |Cite
|
Sign up to set email alerts
|

Importance-Driven Particle Techniques for Flow Visualization

Abstract: Particle tracing has been established as a powerful visualization technique to show the dynamics of 3D flows. Particle tracing in 3D, however, quickly overextends the viewer due to the massive amount of visual information that is typically produced by this technique. In this paper, we present strategies to reduce this amount at the same time revealing important structures in the flow. As an importance measure, we introduce a simple, yet effective clustering approach for vector fields, and we use scalar flow qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Haller [Hal01] has shown that they can be formulated as ridges in the field of the finite‐time Lyapunov exponent [Hal01] (FTLE), measuring the divergence of trajectories, and Lekien et al [LCM*05] have confirmed that LCS behave as material lines (in 2‐D) or material surfaces (in 3‐D). The FTLE‐based approach has recently attracted much interest in the visualization community [BKKW08, STM08], however, it does not in an intrinsic way single out special points, classify them, and characterize their neighbourhood. There is however such a classification for material lines and surfaces, due to Haller [Hal01].…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…Haller [Hal01] has shown that they can be formulated as ridges in the field of the finite‐time Lyapunov exponent [Hal01] (FTLE), measuring the divergence of trajectories, and Lekien et al [LCM*05] have confirmed that LCS behave as material lines (in 2‐D) or material surfaces (in 3‐D). The FTLE‐based approach has recently attracted much interest in the visualization community [BKKW08, STM08], however, it does not in an intrinsic way single out special points, classify them, and characterize their neighbourhood. There is however such a classification for material lines and surfaces, due to Haller [Hal01].…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…Observing moving particles is a powerful way to experience a flow [BKKW08]. To facilitate this experience for a large class of different flows has been the main motivation for our work.…”
Section: Discussionmentioning
confidence: 99%
“…Later they introduced an importance driven scale‐space approach to target visual clutter and information overload in the work of Bürger et al . [BKKW08]. As a different application, Van Pelt et al .…”
Section: Related Workmentioning
confidence: 99%
“…Botchen et al [7] presented a texturebased method using blurred streaklines to convey uncertainty information in two-dimensional flow fields obtained from measurements. A focus-and-context flow visualization method was presented by Bürger et al [8], who combined spatial importance measures with particle glyphs. Specifically for Method of Moments-based simulations, Hlawitschka et al [9] and Hummel et al [10] proposed a visualization approach featuring sampling in addition to parametric bubble glyphs, which were shaped according to local flow properties.…”
Section: Introductionmentioning
confidence: 99%